The Influence of Information Quality and Source Credibility Through Social Media Information Adoption on the Prevention of Deviant Sexual Behavior - Billy Betha Nagara; Iskandar Zulkarnain; Syafruddin Pohan (Riviera Publishing, 2024)
Social media has provided space for adolescents as a source of information in accessing sexuality knowledge that is still taboo to talk about. Sexuality information that is not of good quality and lacks verification will cause adolescents to develop an unbalanced and incorrect understanding of sexuality. This study aims to analyze the influence of information quality and source credibility through the adoption of social media information on the prevention of deviant sexual behaviour in the Youth Information and Counseling Center (PIKR) group in Palembang City. The theories used in this study are the Social Learning Theory and Information Adoption Model. This research uses a quantitative approach with a correlational method. The population and sample in this study were PIKR groups in Palembang City totaling 275 respondents. Sampling using a total sampling technique. Data collection techniques using questionnaires distributed to research respondents. The research data were analyzed using single-table analysis, cross-table analysis and path analysis. The results showed that the quality of information and credibility of the source through the adoption of social media information affect the prevention of deviant sexual behaviour in PIKR groups in Palembang City. The implication of this study shows that improving the quality and credibility of information on social media is very important for the effectiveness of the prevention of deviant sexual behaviour among adolescents.